The Curiosity Club : kid's nature activity book - Roberts, Allene, 1956- (New York : John Wiley & Sons, 1992)
Text and suggested activities give the reader good reasons to be outside where nature uses a special language to talk to us.
Includes index.
Faculty.
Keywords: Natural history -- Study and teaching -- Juvenile literature; Nature study -- Activity programs -- Juvenile literature; Nature study